2021
DOI: 10.1088/1741-4326/abc06c
|View full text |Cite
|
Sign up to set email alerts
|

The reversed field pinch

Abstract: This paper reviews the research on the reversed field pinch (RFP) in the last three decades. Substantial experimental and theoretical progress and transformational changes have been achieved since the last review (Bodin 1990 Nucl. Fusion 30 1717–37). The experiments have been performed in devices with different sizes and capabilities. The largest are RFX-mod in Padova (Italy) and MST in Madison (USA). The experimental community includes also EXTRAP-T2R in Sweden, RELAX in Japan and KTX in Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 619 publications
1
29
0
Order By: Relevance
“…In particular, motivated by the success of the inductive current profile control [31], the first work on the equilibrium reconstruction based on the GS equation was done in [15], which is the only major publication about axisymmetric RFP equilibrium reconstruction to date. Further progress in the RFP research can be found in a recent review of the RFP [34].…”
Section: Related Workmentioning
confidence: 99%
“…In particular, motivated by the success of the inductive current profile control [31], the first work on the equilibrium reconstruction based on the GS equation was done in [15], which is the only major publication about axisymmetric RFP equilibrium reconstruction to date. Further progress in the RFP research can be found in a recent review of the RFP [34].…”
Section: Related Workmentioning
confidence: 99%
“…As these equations show, the direct supply of electromagnetic energy or any force such as the Hall effect or radiation that yields a current density can produce a magnetic field. For example, the origin of a B field in the plasma lab, including a reversed field pinch (RFP; Marrelli et al 2021), is electromagnetic rather than kinetic. Additionally, the effect of the electric force, gravitational force, or inhomogeneously distributed B field can yield various drift motions of the charged particles.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic self-organization processes determine the signature equilibrium configuration of reversed-field pinch (RFP) plasmas (Marrelli et al. 2021) driven by steady induction. In these RFP plasmas, the toroidal magnetic field is peaked in the core, decreases monotonically with minor radius and reverses direction near the plasma edge.…”
Section: Introductionmentioning
confidence: 99%